2018
DOI: 10.3389/fonc.2018.00467
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA From Metastatic Pancreatic Neuroendocrine Tumor Patients Contains Tumor-Specific Mutations and Copy Number Variations

Abstract: Background: Detection of tumor-specific alterations in cell-free DNA (cfDNA) has proven valuable as a liquid biopsy for several types of cancer. So far, use of cfDNA remains unexplored for pancreatic neuroendocrine tumor (PNET) patients.Methods: From 10 PNET patients, fresh frozen tumor tissue, buffy coat and plasma samples were collected. Whole-exome sequencing of primary tumor and germline DNA was performed to identify tumor-specific variants and copy number variations (CNVs). Subsequently, tumor-specific va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…A recent case report suggested that it would be more feasible to sequence a tissue sample from the tumor and then design a personalized ctDNA blood-based or even urine-based assay (273). The latter could be applied to monitor the disease, as recently demonstrated by Boons et al (274), who used this approach to correctly identify three metastatic cases in a set of 10 patients with PanNETs. Another promising approach has been proposed for PanNETs, exploiting whole-exome sequencing on ctDNA (275).…”
Section: Advances In Targeted Therapy and Detection Of Gep-nets In LImentioning
confidence: 97%
“…A recent case report suggested that it would be more feasible to sequence a tissue sample from the tumor and then design a personalized ctDNA blood-based or even urine-based assay (273). The latter could be applied to monitor the disease, as recently demonstrated by Boons et al (274), who used this approach to correctly identify three metastatic cases in a set of 10 patients with PanNETs. Another promising approach has been proposed for PanNETs, exploiting whole-exome sequencing on ctDNA (275).…”
Section: Advances In Targeted Therapy and Detection Of Gep-nets In LImentioning
confidence: 97%
“…We have therefore performed the CNA calling only on the EPIC study cohort, for which good normal control samples and more data points were available, given the large number of probes on the EPIC DNA methylation arrays. To validate CNA calling on the methylation data, we compared the CNA profile based on DNA methylation analysis with the CNA profile based on whole-exome sequencing (WES) analysis for two tumors where both types of data were available [27]. Results were very comparable between CNAs on WES and on the methylation data ( Figure S1).…”
Section: Copy Number Alterations Are Different Between the Two Subtypesmentioning
confidence: 99%
“…Whole-exome sequencing of 22 patients (UZA-01-UZA-10 and Lawrence-001-Lawrence-012) and deep targeted sequencing of 3 patients (Lawrence-013-Lawrence-015) has been performed in previous studies [21,27]. The identified variants in MEN1, DAXX and ATRX were validated using Sanger sequencing, if the allelic ratio was high enough, and are summarized in Table 2.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Furthermore, up to 43% of the patients have a mutually exclusive mutation in ATRX or DAXX (Jiao et al 2011). In addition, a recent publication demonstrated the presence of DAXX mutations in circulating tumor DNA of pNET patients (Boons et al 2018). Losses of chromosomal regions including MEN1 are observed in 70% of sporadic pNETs (Scarpa et al 2017).…”
Section: Pi3k/akt/mtor Signaling In Neuroendocrine Tumorsmentioning
confidence: 99%